Optimalisasi Peran Dakwah Ulama Dalam Mensosialisasikan Pencegahan Pernikahan Dini Di Nusa Tenggara Barat - Lalu Ahmad Zaenuri; Andri Kurniawan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2023)
This study aims to determine the involvement and role of ulama in preventing early-age marriage in West Nusa Tenggara. The government has implemented a limitation on the age of marriage, but for the people of West Nusa Tenggara, it requires the role of Ulama in socializing and convincing the public to do this. This rule needs to be seen from the side of the social welfare of the community. This study uses a qualitative descriptive approach with the type of library research. Data collection techniques using the literature review through various references related to research. The results of the research through a literature review are looking at government programs such as those related to early-age marriage, then the stakeholders involved are not enough from government agencies only. It’s also important the involvement and role of ulama as role models for the community in suppressing cases of early-age marriage through da'wah communication activities and forming special guidance and assistance programs for parents and adolescents regarding the negative impacts on early-age marriage.